Transition-Metal-Catalysed Transfer Hydrogenation Reactions with Glycerol and Carbohydrates as Hydrogen Donors - Ansari M.F.; Anshika; Sortais J.-B.; Elangovan S. (My University, 2025)
Catalytic transfer hydrogenation is a practical approach for reduction of various unsaturated compounds and an alternative to pressurised hydrogenation and traditional metal hydride reagents. Among the various hydrogen donors, biomass such as glycerol and carbohydrates received considerable attention for the reduction reactions due to their non-toxic, eco-friendly and renewable nature. The present review addresses the development of homogeneous and heterogeneous catalysts for the transfer hydrogenation of carbonyl compounds, alkenes, alkynes, nitro compounds, CO2 etc. using glycerol and carbohydrates as potential hydrogen donors. © 2024 Wiley-VCH GmbH.